HYPERREALITY IS GETTING REAL: A LITERATURE REVIEW - Grazzia Tapparan; Irmawan Rahyadi (Jurnal Scientia, 2023)
The relationship between the media and today's reality cannot be separated. The media is growing with increasingly sophisticated technology to become an unavoidable intermediary between humans and reality. However, with Baudrillard's theory of hyperreality, the media is no longer seen only as an intermediary. Still, there can be bias that can change the idea of reality that reaches humans. This paper collects how the idea of hyperreality appears on various occasions involving media. Yes, hyperreality seems to be getting real.